2014
DOI: 10.1016/j.febslet.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐suppressive microRNA‐224 inhibits cancer cell migration and invasion via targeting oncogenic TPD52 in prostate cancer

Abstract: Edited by Tamas DalmayKeywords: miR-224 TPD52 Prostate cancer microRNA Tumour suppressor a b s t r a c t Our recent study of the microRNA expression signature of prostate cancer (PCa) revealed that microRNA-224 (miR-224) is significantly downregulated in PCa tissues. Here, we found that restoration of miR-224 significantly inhibits PCa cell migration and invasion. Additionally, we found that oncogenic TPD52 is a direct target of miR-224 regulation. Silencing of the TPD52 gene significantly inhibits cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 43 publications
(87 reference statements)
0
45
0
Order By: Relevance
“…Lin et al revealed that reduced expression of miR-224 in prostate cancer was associated with metastasis, high PSA level, high Gleason scores, and poor biochemical recurrence-free survival [25]. Forced expression of miR-224 suppressed prostate cancer cell proliferation, invasion and migration, and promoted cell apoptosis [17,25]. MiR-224 expression has also been found to correlate inversely with tumor stage and lymph node metastasis as well as survival times in colorectal cancer patients [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al revealed that reduced expression of miR-224 in prostate cancer was associated with metastasis, high PSA level, high Gleason scores, and poor biochemical recurrence-free survival [25]. Forced expression of miR-224 suppressed prostate cancer cell proliferation, invasion and migration, and promoted cell apoptosis [17,25]. MiR-224 expression has also been found to correlate inversely with tumor stage and lymph node metastasis as well as survival times in colorectal cancer patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified many oncogenes or tumor suppressor genes as direct targets of miR-224, such as apoptosis inhibitor 5 (API5) [19], Homeobox D10 (HOXD10) [20], SMAD family member 4 (SMAD4) [33], SMAD family member 5 (SMAD5 [18], sarcolemma-associated protein (SLMAP) [18], Type 1 iodothyronine deiodinase (DIO1) [21], tumour protein D52 (TPD52) [17], tribbles homolog 1 (TRIB1) [25], chemokine (C-X-C motif) receptor 4 (CXCR4) [34], hypoxia-inducible factor 1 (HIF1A) [35], Raf kinase inhibitor protein (RKIP) [30], and cell division control protein 42 (CDC42) [36]. It is now clear that miRNAs execute their oncogenic or tumor suppressive functions by regulating the expression of target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that TPD52 was overexpressed in several cancers, and function as an oncogenes [29, 30]. Recent study indicated that miR-145-5p and its target gene TPD52 contributed to malignancy progression and in metastasis of brain tumor [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-224 can bind to the tumor suppressors of TNFα-induced protein 1 (TNFAIP1) and Smad4, Raf kinase inhibitor protein (RKIP), apoptosis inhibitor-5 (API-5), PH domain leucine-rich-repeat protein phosphatase 1 (PHLPP1), and PHLPP2 to promote the survival and proliferation of colorectal cancer (CRC) and hepatocellular carcinoma (HCC), but bind to the TRIB1 to promote apoptosis of prostatic cancer cells [711]. Furthermore, miR224 binds to the Smad4 and Homeobox D10 (HOXD10) to promote migration of HCC and CRC [8, 12] while it binds to the TPD52 to inhibit migration of prostatic cancer PCa cells [13]. Apparently, the regulatory effects of miR-224 are tissue-specific and depend on the dynamic balance of different signal pathways that regulate proliferation, apoptosis and migration of cancer cells.…”
Section: Introductionmentioning
confidence: 99%